Reply to the comment by Iyer and Schmid on "Thickness matters: Influence of dolerite sills on the thermal maturity of surrounding rocks in a coal bed methane play in Botswana" by Bulguroglu, M.E., Milkov, A.V., Marine and Petroleum Geology 111 (2020), 219-229. (May 2020) - Bulguroglu, Muhammed Emin; Milkov, Alexei V.
Highlights: The model of Iyer and Schmidt (2020) may have higher resolution, but it is not supported by actual subsurface data and has questionable usefulness. Many other researchers reported cases where thin dolerite sills and dykes have large normalized thermal aureoles. We outlined in the original paper several processes that may explain why thin sills have large normalized thermal aureoles..